Sistem Kontrol Nutrisi Otomatis pada Tanaman Tomat Berbasis Arduino - Sri Kurniyan Sari; Supriadi Sahibu; Zahir Zainuddin3; Fajar Husain A (Jurnal Teknik Informatika dan Teknologi Informasi, 2024)
This research aims to develop an automatic nutrient delivery system for tomato plants in order to ensure optimal nutrient concentration and reduce manual labor during cultivation. The system is designed using a TDS sensor to measure nutrient concentration in water, a water level sensor to monitor the volume of solution in the nutrient container, and a relay module to control the activation of the nutrient pumps and circulation pump. The microcontroller processes sensor readings and regulates the addition of nutrients when the concentration falls below the preset threshold. Tests were conducted to evaluate sensor accuracy, pump responsiveness, and the system’s overall performance in maintaining nutrient stability. The results indicate that the water level sensor accurately detects changes in water volume, the TDS sensor successfully measures PPM values above 1400, and both nutrient pumps operate effectively to dispense nutrient solutions as required. The circulation pump also functions properly in distributing the nutrient-enriched water into the hydroponic pipes. These findings demonstrate that the proposed Arduino-based automatic nutrient system is capable of maintaining appropriate nutrient levels for tomato cultivation, supporting more efficient and consistent hydroponic plant growth.